The First Salamander Defensin Antimicrobial Peptide - Meng, Ping (Public Library of Science, 2013)
Antimicrobial peptides have been widely identified from amphibian skins except salamanders. A novel antimicrobial peptide (CFBD) was isolated and characterized from skin secretions of the salamander, Cynops fudingensis. The cDNA encoding CFBD precursor was cloned from the skin cDNA library of C. fudingensis. The precursor was composed of three domains: signal peptide of 17 residues, mature peptide of 41 residues and intervening propeptide of 3 residues. There are six cysteines in the sequence of mature CFBD peptide, which possibly form three disulfide-bridges. CFBD showed antimicrobial activities against Staphylococcus aureus, Bacillus subtilis, Candida albicans and Escherichia coli. This peptide could be classified into family of β-defensin based on its seqeuence similarity with β-defensins from other vertebrates. Evolution analysis indicated that CFBD was close to fish β-defensin. As far as we know, CFBD is the first β-defensin antimicrobial peptide from salamanders.